Determinación de las curvas de absorción de agua en diferentes cadenas de hidratación y su influencia en la duración de vida en florero, de la variedad de rosa sexy red en la empresa Floreloy S.A. - Cañizares Cisneros, Mónica Alexandra (2008)
During the period December 2007 to July 2008 were carried out the investigation to determine the curves of water absorption in different hydrate periods and their influence in the duration of life in vase, of the variety of rose Sexy red in the Company Floreloy S.A, located in the county of Pichincha, canton Cayambe, parish Cangahua. The volume of water was measured absorbed by the stem in the different hydrate stages, as well as the total absorbed in the chain of the process post-crop; the existent relationship was determined between the hydrate and the weight of the stem in the different stages of the process post-crop, the effect of the use of the hydrate solutions was evaluated, in the process of absorption of water during the hydrate chain and its influence in the duration of life in vase and the floral longevity was quantified considered as the number of days starting from the moment in that the shafts are placed in vase until its nod.